Hearts and Homes: The Potential of Conservation Laser Cleaning for Post-disaster Wellbeing and Waste Reduction. (10th August 2022) - Wain, Alison; Rode, Andrei; Wilkinson, Sara; Banishemi, Saeed; Hirajasouli, Aso; Rapp, Ludovic
ABSTRACT: This paper explores the potential for conservators to use their unique combination of materials and heritage experience to tackle the challenges of recovery in fire-affected areas, helping to minimise the waste and greenhouse gas emissions associated with traditional processes of post-disaster building remediation by facilitating cleaning and repair rather than replacement and disposal of fire-affected materials. The focus is not on saving 'special' items, but on remediating the broader fabric of homes and possessions that embody a sense of place and identity that sustains wellbeing and aids recovery after disaster. The samples used are painted plasterboard affected by smoke from the 2019 bushfires on the south-eastern coast of Australia. The method being trialled is the use of lasers to remove ash (soot) deposited by the smoke, to achieve a reduction in visual reminders of the fire and a surface that is ready for processes such as sanding, plastering or repainting to prepare a home for quick post-disaster re-occupation. Lasers have been extensively used for cleaning buildings. They use light energy to clean, so do not require abrasives or other chemicals, or touching of the surface. Nanosecond and femtosecond pulse lasers are trialled, and the effectiveness of the laser cleaning is analysed using visual assessment, optical microscopy, spectrophotometry and Fourier transform infrared (FTIR) spectroscopy.